Improved land reforms to the benefit of women´s access to land to foster and support social norm change, a case study of Western Area rural district and Bombali district in Sierra Leone - Bankolay Theodore Turay; Modupe Moronke Omirin (African Journal on Land Policy and Geospatial Sciences)
It is critical to have land policies that facilitate access to and effective control of land and other natural resources to achieve inclusive growth and eradicate poverty. It is well known that discrimination in land rights occurs globally, both in formal and customary settings. The reason for this is that land rights are either strong or weak and are held by a variety of groups of people. It is the weaker variants of the inequalities that stifle tenure security, reduce land use, and threaten the food security of those who depend on the land to survive. This study looks at improved land reforms to the benefit of women´s access to land to foster and support social norm change in Sierra Leone. A Cross-sectional research design was used for data collection. Quantitative data were analyzed descriptively; while, qualitative data were analyzed using content analysis. A household survey across the settlements for semi-structured questionnaire administration. In-depth interviews of the various category of women and household heads through a purposive sampling technique. Key informant interviews (KII) consisted of local leaders, household heads, women leaders and community land owners. An unrefined search using keywords through JSTOR, Google Scholar, Research Gate and UNILAG database yielded search results of journals, book chapters and research reports on the subject. This was restricted to the utilization of accessible resources drawing on sources from different scholastic disciplines while performing an area audit. The results of the study indicated that the principle that statutory reforms automatically take precedence over other laws in cases where there is a conflict between laws seems to remain on paper here. When it comes to land, informal and customary arrangements dominate and custom is seen to be powerful, authoritative and even unshakable. Even with the current gender-equitable legal framework, proper implementation of these laws is often lacking and enforcement institutions are weak.  Therefore, it is recommended that increased efforts are needed to assist women in exercising their legal rights, such as addressing norms and customs regarding how women acquire land (such as through purchase or inheritance), the quality of the land they receive, and how land is transferred upon marriage or the death of a spouse.